AN INTERPERSONAL ANALYSIS OF THREE SELECTED LESSONS IN THE BOOK “EXPLORING SCIENCE 5” - Ta, Thi Thu Hang (VNU Journal of Foreign Studies, 2024)
The study investigates the interpersonal meanings expressed through the mood and modality resources presented in the textbook “Exploring Science 5” authored by Penny Johnson and Mark Levesley. This textbook is employed in the instruction of fifth-grade science in various countries, including the United States. The analysis is conducted within the theoretical framework of Systemic Functional Linguistics (SFL). The results reveal a notably high occurrence of declarative clauses used in the corpus of the three lessons, whereas interrogative and imperative clauses constitute a modest proportion. Regarding modality, the use of modality in the corpus of the three lessons is not extensive and mainly involves modality conveying “probability” and “obligation”. These results suggest that the authors frequently shape knowledge in a particular manner that is aligned with the style of scientific texts.